Case report: Sustained remission after combined sintilimab, anti-VEGF therapy, and chemotherapy in a patient with non-small cell lung cancer harboring acquired EGFR 19Del/T790M/cis-C797S mutation resistance - He, Wanming; Tong, Lihua; Yang, Wen; Yuan, Yanling; Li, Yu; Tang, Wubing (Frontiers in Oncology, 2024)
Third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) are highly effective against tumors harboring the T790M mutation. However, patients treated with these inhibitors ultimately develop resistance, and the most common mechanism is the emergence of the EGFR C797S mutation. Few treatment regimens have been reported for this condition. In this report, we present a successful combination treatment with the programmed cell death 1 (PD-1) inhibitor sintilimab, anti-vascular endothelial growth factor (VEGF) therapy, and chemotherapy with pemetrexed and cisplatin in a patient with non-small cell lung cancer (NSCLC) who developed acquired resistance with EGFR 19 exon deletion (19Del)/T790M/cis-C797S mutation following progression with ametinib therapy. This regimen was well tolerated, and the patient has remained progression-free for 15 months. Our case provides clinical evidence that the combination of PD-1 inhibitor, anti-VEGF therapy, and chemotherapy may be an efficacious therapeutic strategy for NSCLC patients with acquired EGFR 19Del/T790M/cis-C797S mutation resistance following progression with EGFR TKI therapy.